The pan-HDAC inhibitor panobinostat acts as a sensitizer for erlotinib activity in EGFR-mutated and -wildtype non-small cell lung cancer cells. Issue 1 (December 2015) - Greve, Gabriele; Schiffmann, Insa; Pfeifer, Dietmar; Pantic, Milena; Schüler, Julia; Lübbert, Michael
Abstract Background The receptor tyrosine kinase (RTK) EGFR is overexpressed and mutated in NSCLC. These mutations can be targeted by RTK inhibitors (TKIs) such as erlotinib. Chromatin-modifying agents may offer a novel therapeutic approach by sensitizing tumor cells to TKIs. Methods The NSCLC cell lines HCC827 (EGFR mutant, adenocarcinoma), A549 (EGFR wt, adenocarcinoma) and NCI-H460 (EGFR wt, large cell carcinoma) were analyzed by SNP6.0 array. Changes in proliferation after panobinostat (LBH-589, PS) and erlotinib treatment were quantified by WST-1 assay and apoptosis by Annexin V/7-AAD flow cytometry. Abundance of target proteins and histone marks (acH3, H3K4me1/2/3) was determined by immunoblotting. Results As expected, theEGFR wt cell lines A549 and NCI-H460 were quite insensitive to the growth-inhibitory effect of erlotinib (IC50 70-100 μM), compared to HCC827 (IC50 < 0.02 μM). All three cell lines were sensitive to PS treatment (IC50 : HCC827 10 nM, A549 20 nM and NCI-H460 35 nM). The combination of both drugs further reduced proliferation in HCC827 and in A549, but not in NCI-H460. PS alone induced differentiation and expression of p21WAF1/CIP1 and p53 and decreased CHK1 in all three cell lines, with almost no further effect when combined with erlotinib. In contrast, combination treatment additively decreased pEGFR, pERK and pAKT in A549. Both drugs synergistically induced acH3 in the adenocarcinoma lines. Surprisingly, we also observed induction of H3K4 methylation marks after erlotinib treatment in HCC827 and in A549 that was further enhanced by combination with PS. Conclusion PS sensitized lung adenocarcinoma cells to the antiproliferative effects of erlotinib. In these cell lines, the drug combination also had a robust, not previously described effect on histone H3 acetylation and H3K4 methylation.